(untitled) (The Research of Medical Science Review, 2025)
Evidence-Based Practice (EBP) is recognized globally as a cornerstone for delivering high-quality, patient-centered care. Despite its importance, numerous barriers hinder its adoption among nurses, particularly in developing countries. This descriptive cross-sectional study was conducted at Mardan Medical Complex (MMC), a tertiary care hospital in Pakistan, to assess the barriers nurses face in learning and implementing EBP. A total of 110 registered nurses participated using a validated questionnaire designed to identify challenges related to knowledge, attitude, organizational support, and implementation. The findings revealed that limited access to resources (90.9%), lack of time (81.8%), insufficient authority (79.0%), and inadequate knowledge and training (60%) were among the primary barriers. Additionally, organizational culture, lack of mentorship, and resistance to change further impeded EBP integration. The study highlights the urgent need for institutional strategies, including continuous professional development, organizational support, and policy reform to foster an environment conducive to EBP. Addressing these barriers is crucial to improving clinical decision-making, enhancing patient outcomes, and advancing nursing practice within healthcare systems like MMC.